Feasibility of trancutaneous auricular vagus nerve stimulation in Black and Hispanic/Latino people with peripheral neuropathy - Wong, Marlon L.; Widerström-Noga, Eva; Bolanos, Jessica L.; Gonzalez, Gabriel; Penedo, Frank J.; Hosein, Peter J.; Tovin, Melissa M.; Gonzalez, Juan P.; McTeague, Lisa M. (Frontiers in Pain Research, 2025)
IntroductionPeripheral neuropathy (PN) is the most common neurodegenerative disorder, and the primary causes are chemotherapy-induced peripheral neuropathy (CIPN) and diabetic neuropathy (DN). Transcutaneous auricular vagus nerve stimulation (taVNS) is a promising non-pharmacological and non-invasive intervention that targets key pathways involved with PN. However, research is needed to determine the feasibility, acceptability, and effects of taVNS in people with PN. It is also critical that this research on taVNS include the perspectives of Black and Hispanic/Latino patients, who are often underrepresented in research.MethodsThis research was comprised of two consecutive studies: a survey and a pilot randomized sham-controlled trial (RCT). The survey assessed symptom burden, management strategies, and interest in taVNS among CIPN patients. The pilot RCT evaluated the feasibility, acceptability, and preliminary effects of taVNS in Black and Hispanic/Latino patients with CIPN or diabetic neuropathy. Participants were recruited from the University of Miami medical system, with culturally sensitive approaches to enhance minority participation.ResultsThe survey included 62 respondents, 78% Black or Hispanic/Latino, revealing high symptom burden and significant interest in taVNS (82% expressed moderate to high interest). The pilot RCT enrolled 28 participants, achieving a 42% recruitment rate and 86% retention. taVNS was well tolerated, with no significant adverse effects. Preliminary data indicated a decrease in neuropathic symptoms and an increased heart rate variability (HRV) during active taVNS, suggesting autonomic modulation. Tingling sensation and pain decreased by median values of 2.0 and 1.5, respectively. Additionally, the median values for standard deviation of the RR interval increased from 34.9 (CI = 21.6–44.8) at baseline to 44.8 (CI = 26.5–50.3) during intervention. Exit interviews highlighted positive participant experiences and identified potential barriers, such as protocol length and distrust in medical research.ConclusionThe findings underscore the need for novel CIPN treatments and demonstrate the feasibility of conducting taVNS research in historically underrepresented populations. High interest in taVNS and successful recruitment and retention rates suggest that culturally sensitive approaches can enhance minority participation in clinical trials. These findings will be used to develop a large clinical trial to determine the efficacy of repeated taVNS in a diverse cohort. Clinical Trial Registrationhttps://clinicaltrials.gov, identifier (NCT05896202).